2010
DOI: 10.1088/1674-1056/19/3/038601
|View full text |Cite
|
Sign up to set email alerts
|

Polymer solar cells based on a PEDOT:PSS layer spin-coated under the action of an electric field

Abstract: Feng Zhi-Hui(冯志慧) a) , Hou Yan-Bing(侯延冰) a) † , Shi Quan-Min(师全民) a) , Qin Li-Fang(秦丽芳) a) , Li Yan(李 妍) a) , Zhang Lei(张 磊) a) , Liu Xiao-Jun(刘小君) a) , Teng Feng(腾 枫) a) , Wang Yong-Sheng(王永生) a) , and Xia Rui-Dong(夏瑞东) b)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
(17 reference statements)
3
10
0
Order By: Relevance
“…Since the conductivity is mainly because of PEDOT, 7 several approaches for enhancement of the PEDOT to PSS ratio in the deposited film (which in turn results in the conductivity enhancement) are reported. These include mixing with organic solvents, [8][9][10] application of electric field during spin coating, 11 salt or acid treatment, 12 and thermal annealing. 7 The PSS content is reduced, when spin coating of PEDOT: PSS is done under the action of electric field, which results in the enhancement of film conductivity as well as organic solar cell performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the conductivity is mainly because of PEDOT, 7 several approaches for enhancement of the PEDOT to PSS ratio in the deposited film (which in turn results in the conductivity enhancement) are reported. These include mixing with organic solvents, [8][9][10] application of electric field during spin coating, 11 salt or acid treatment, 12 and thermal annealing. 7 The PSS content is reduced, when spin coating of PEDOT: PSS is done under the action of electric field, which results in the enhancement of film conductivity as well as organic solar cell performance.…”
mentioning
confidence: 99%
“…7 The PSS content is reduced, when spin coating of PEDOT: PSS is done under the action of electric field, which results in the enhancement of film conductivity as well as organic solar cell performance. 11 It is reported that conductivity of PEDOT:PSS get enhanced by the addition of DMSO, DMF, TMS, aqueous solution of zwitterions, etc., because of the screening effect between PEDOT and PSS chains. [13][14][15] The reorientation of PEDOT chains are also reported by the addition of solid sorbitol, which results in the conductivity enhancement.…”
mentioning
confidence: 99%
“…Spin coating of polymers, such as MEH-PPV, PEDOT:PSS, etc. under a static electric field is also reported by some research groups [3,4]. Zhao et al applied a high AC electric field with ultralow frequency to orient P3HT polymers in P3HT:PCBM blend active layer immediately after the spin coating [5].…”
Section: Introductionmentioning
confidence: 68%
“…Increased electrical carrier mobility in organic semiconductors is known to build higher efficiency solar cells. Recently several research groups have applied electric field at various stages of devices fabrication to orient the polar molecules in order to have improved charge mobility [1][2][3][4][5][6][7][8][9]. Some research groups have applied reverse bias across the fully fabricated devices during post-production thermal annealing [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of the electric field treatments have been reported in literature. The early research with DC electric field treatment was done at spin-coating stage or not at an elevated temperature (room temperature drying) [23][24][25]. It was pointed out that the DC electric field postproduction treatment needs to be at elevated temperature to be effective [11,26,27].…”
Section: Introductionmentioning
confidence: 99%